2017
DOI: 10.1007/s13204-017-0550-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polystyrene incorporated with gold and silver nanoparticles for optoelectronic applications

Abstract: In this paper, methyl-orange-doped polystyrene (PS) microspheres covered with gold and silver nanoparticles (NPs) have been synthesized. The optical and structural properties of the porous polystyrene films before and after incorporation of Au and Ag nanoparticles were investigated using X-ray diffraction (XRD), scanning electron microscope (SEM), atomic force microscope (AFM), Fourier transformation infrared spectrophotometer (FT-IR), and UV-Vis spectrophotometer. The optical data showed that the optical ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Interestingly, 1633 cm -1 and 3440 cm -1 wavenumbers were not detected during the analysis because of the elimination of chemical compounds after treatment using nitrogen plasma. Wavenumbers of 500-1600 cm -1 confirm C-H and C-C bonds (Singh et al, 2015;Ismail et al, 2017). In this study, peaks in the range 500-1600 cm -1 were detected in the final residue, which were C-H bonds and C-C bonds, confirming the transformation of carbon to H 2 and CH 4 .…”
Section: Characterization Analysis Of Psfsupporting
confidence: 72%
“…Interestingly, 1633 cm -1 and 3440 cm -1 wavenumbers were not detected during the analysis because of the elimination of chemical compounds after treatment using nitrogen plasma. Wavenumbers of 500-1600 cm -1 confirm C-H and C-C bonds (Singh et al, 2015;Ismail et al, 2017). In this study, peaks in the range 500-1600 cm -1 were detected in the final residue, which were C-H bonds and C-C bonds, confirming the transformation of carbon to H 2 and CH 4 .…”
Section: Characterization Analysis Of Psfsupporting
confidence: 72%
“…Over the past decades, various applications of the SPR of Ag NPs have been revealed, particularly in biosensing, surface-enhanced Raman scattering, and plasmon circuitry [ 36 ]. Ismail et al [ 37 ], revealed that polymer composites incorporated with Ag nanoparticles are crucial in fabricating high photosensitivity and cost-effective PS/Si heterojunctionphotodetectors. According to the recent review ofJeong et al [ 38 ], silver NPs are promising plasmonic materials for application in organic optoelectronic devices including organic light-emitting diodes (OLEDs) and polymer solar cells (PSCs).…”
Section: Resultsmentioning
confidence: 99%
“…While the application of noble metal nanostructures in plasmonic devices has been well established, the performance of noble metals supported over semiconductors and dielectric matrices has been exploited successfully in catalytic and photocatalytic reactions, 3,6,7 alongside other optoelectronic applications. 8 However, the use of bare noble metal nanostructures in catalysis or photocatalysis has been limited. 9,10 While the most promising utilizations of bare noble metal nanostructures have been the bio-sensing based on surface enhanced Raman scattering (SERS) or electrochemical response 11,12 and bioremediation, 13 they have also been utilized, although not so frequent, for catalytic degradation/reduction of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%